MENGAGAS CONSTITUTIONAL COMPLAINT DALAM KONSTITUSI INDONESIA DAN POLITIK HUKUM ISLAM - Kusumo, Bambang Ali; Jaelani, Abdul Kadir (Wacana Hukum, 2018)
This paper discuss constitutional complaint as laws effort to the violation of constitutional right of civil. The protection of human basic right in the next called constitution right was the one of pure element should be contain in the constututional country. UUD 1945 as basic constitutional of Indonesia contrastly admit and protect civil right constitution, but in reality, many case which complaint to the constition departement that indicated violated constitution right because the laws spread out bay government, on the other hand all effort have done by the complainer can not be justicated. Because of that, appear the ideas of constitutional complaint. constituional complaint is constitution which complaining by the complainer because the ommision of public government which is guessed violated constitutional right of complainer. constitutional complaint in generally can be proposed if all laws effort which here has done or no laws effort again.